CEMARAN BAKTERI MESOFILIK AEROBIK PADA CEKER AYAM DALAM SOTO DARI TIGA LOKASI RUMAH MAKAN DI BANDA ACEH (Mesophilic Aerobic Bacteria Contamination of chicken shank in soto from three restaurant locations in Banda Aceh) - Teuku Reza Ferasyi; Razali Razali; Safarwati Safarwati; Nurliana Nurliana; Sulasmi Sulasmi; T. Armansyah (Universitas Syiah Kuala, 2015)
This study was aimed to test the level of mesophilic aerobic bacteria contamination on chicken shank in